2017
DOI: 10.1177/1753193417744420
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematics of the lunate, hamate, capitate and triquetrum with type 1 or 2 lunate morphology

Abstract: The purpose of this study was to investigate the differences in three-dimensional carpal kinematics between type 1 and 2 lunates. We studied 15 instances of wrist flexion to extension (nine type 1, six type 2), 13 of radial to ulnar deviation (seven type 1, six type 2), and 12 of dart-throwing motion (six each of type 1 and 2) in 25 normal participants based on imaging with computerized tomography. Mean proximal translation of the distal articular midpoint of the triquetrum relative to type 2 lunates during wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There were very small 95% CIs in measurements of FE and RUD wrist motion (Figure 5) indicating that the scapholunate motion patterns in our participant population aged 20 to 40 years were very similar. This was an unexpected finding, since two other studies found that differences in lunate morphology affect carpal kinematics (Abe et al., 2017; Bain et al., 2015). The lunate morphology in the participants in our study consisted of 24 type 1 lunates and 18 type 2 lunates, but lunate morphology did not seem to influence scapholunate kinematics in our study.…”
Section: Discussionmentioning
confidence: 66%
“…There were very small 95% CIs in measurements of FE and RUD wrist motion (Figure 5) indicating that the scapholunate motion patterns in our participant population aged 20 to 40 years were very similar. This was an unexpected finding, since two other studies found that differences in lunate morphology affect carpal kinematics (Abe et al., 2017; Bain et al., 2015). The lunate morphology in the participants in our study consisted of 24 type 1 lunates and 18 type 2 lunates, but lunate morphology did not seem to influence scapholunate kinematics in our study.…”
Section: Discussionmentioning
confidence: 66%
“…This would seem to support more ulnarly translated forces in type 2 lunate wrists. 12 However, this more "stable" column, while transferring compression to the triquetrohamate joint, may actually cause shear forces to be transmitted to the area of least resistance, i.e., more radially, into the more mobile scapholunate interosseous ligament (SLIL) area. Furthermore, the forces may differ in the different wrist positions, and while most of the load is transferred ulnarly in ulnar deviation of a type 2 wrist, this may differ in radial or neutral deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of carpal bone collision using finite element modeling might yield higher accuracy with a refined model. Additionally, it has been shown that the lunate has two main anatomical shapes, and two different motion paths have been proposed for it; we did not consider effects of bone shapes in our modeling (although we accounted for the size by scaling all carpal bones). Further studies need to examine the influence of the differing shapes of carpal bones on the wrist kinematics.…”
Section: Discussionmentioning
confidence: 99%